“Looking for a Better Future”: Examining African Portuguese-Speaking Students’ Motivation to Study in Portuguese Higher Education - Catarina Doutor, Natália Alves (Educational Process: International Journal)
Background/purpose. While the existing literature explores the internalization of higher education, a significant gap remains in comprehending the motivations behind international students choosing Portuguese higher education. This study aims to address this gap by examining the motivations of a specific group within Portuguese universities: international students from Portuguese-speaking African countries.